Highly conserved epigenetic regulation of BOULE and DAZL is associated with human fertility. Issue 10 (29th June 2016) - Zhang, Chenwang; Xue, Peng; Gao, Liuze; Chen, Xia; Lin, Kaibo; Yang, Xiaoyu; Dai, Yifan; Xu, Eugene Yujun
ABSTRACT: Separation of germ cells from somatic cells is a widespread feature of animal sexual reproduction, with a core set of germ cell factors conserved among diverse animals. It is not known what controls their conserved gonad‐specific expression. Core components of epigenetic machinery are ancient, but its role in conserved tissue expression regulation remains unexplored. We found that promoters of the reproductive genes BOULE and DAZL exhibit differential DNA methylation, consistent with their gonad‐specific expression in humans and mice. Low or little promoter methylation from the testicular tissue is attributed to spermatogenic cells of various stages in the testis. Such differential DNA methylation is present in the orthologous promoters not only of other mammalian species, but also of chickens and fish, supporting a highly conserved epigenetic mechanism. Furthermore, hypermethylation of DAZL and BOULE promoters in human sperm is associated with human infertility. Our data strongly suggest that epigenetic regulation may underlie conserved germ‐cell–specific expression, and such a mechanism may play an important role in human fertility.—Zhang, C., Xue, P., Gao, L., Chen, X., Lin, K., Yang, X., Dai, Y., Xu, E. Y. Highly conserved epigenetic regulation of BOULE and DAZL is associated with human fertility. FASEB J. 30, 3424–3440 (2016). www.fasebj.org